2005
DOI: 10.1111/j.1742-4658.2005.05025.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures for amyloid fibrils

Abstract: Alzheimer's disease and Creutzfeldt–Jakob disease are the best‐known examples of a group of diseases known as the amyloidoses. They are characterized by the extracellular deposition of toxic, insoluble amyloid fibrils. Knowledge of the structure of these fibrils is essential for understanding the process of pathology of the amyloidoses and for the rational design of drugs to inhibit or reverse amyloid formation. Structural models have been built using information from a wide variety of techniques, including X‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
419
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 426 publications
(441 citation statements)
references
References 105 publications
14
419
1
7
Order By: Relevance
“…X-ray fiber diffraction showed that the samples of pure A␤ and mixed ratios all exhibit the classic cross-␤ fiber diffraction patterns described in the literature (38,39), showing a strong meridional reflection at 4.7 Å and a major equatorial reflection at ϳ10 Å consistent with a cross-␤ architecture (Fig. 3B).…”
Section: Direct Interactions Between A␤mentioning
confidence: 61%
“…X-ray fiber diffraction showed that the samples of pure A␤ and mixed ratios all exhibit the classic cross-␤ fiber diffraction patterns described in the literature (38,39), showing a strong meridional reflection at 4.7 Å and a major equatorial reflection at ϳ10 Å consistent with a cross-␤ architecture (Fig. 3B).…”
Section: Direct Interactions Between A␤mentioning
confidence: 61%
“…In vitro experiments have provided evidence supporting the capability of a large variety of proteins and peptides, including those unrelated to any disease, to self-assemble into amyloid fibrils or amyloid-like structures when incubated under appropriate solution conditions. This has led to the suggestion that the ability to form amyloid fibrils is a fundamental property of polypeptide chains (Glenner et al 1974;Kirschner et al 1987;Maggio and Mantyh 1996;Fändrich and Dobson 2002;Makin and Serpell 2005;Chiti and Dobson 2006;Goldschmidt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The best mechanistically characterized examples involve the polymerization of aggregationprone peptides (10,11) or small proteins to give well-defined fibrils based on a regular repeat structure (12)(13)(14)(15)(16)(17)(18). The fibrillar aggregates have a characteristic cross-β X-ray diffraction pattern and bind such dyes as Congo Red and Thioflavine T (ThT) (16). The kinetics of aggregation usually follow a nucleation-growth mechanism, with very slow nucleation (19)(20)(21).…”
mentioning
confidence: 99%